(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
In 1899 Ricciotti Garibaldi headed to Latin America to implement a project with the dual purpose of deterring the encroachments of the indigenous population along the Chilean frontieras and encouraging the employment of Italian emigrants who were to engage in the colonization of Patagonia. In return, the settlers themselves would obtain, as compensation to armed vigilance, a free concession of the land they controlled. The article, through unpublished archive documentation, particularly highlights the political and economic problems that led to the sinking of the project, which was questioned both by the political and diplomatic world, together with the Italian and international press even before being approved by the Argentine government.